INOVASI TEKNOLOGI BERBASIS E-COMMERCE UNTUK MENDORONG UMKM DALAM TRANSFORMASI DENGAN PRINSIP BISNIS SYARIAH - Hikmah Dzil Hijjah; Amanda Tri Utami (Media Riset Bisnis Manajemen Akuntansi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an important part of the Indonesian economy, but many MSMEs still have difficulty using technology and transforming into sharia-based businesses. This study aims to analyze how technological innovation, especially e-commerce, can help MSMEs adapt to sharia business principles. Using a qualitative approach and literature study, this study examines the literature on sharia e-commerce, digital innovation, and the development of MSMEs in the digital era. The results show that e-commerce has great potential to expand the market, increase efficiency, and support sharia transactions such as interest-free financing. In addition, cooperation between digital platforms and sharia financial institutions can strengthen the halal economy. However, challenges such as low digital literacy, lack of infrastructure, and competition from large companies still exist. Therefore, it is important for all parties to cooperate to encourage the digitalization of MSMEs in an inclusive manner and in accordance with Islamic values. Keywords : MSMEs, e-commerce, technology innovation, sharia business, digital transformation.